PENGARUH GROSS PROFIT MARGIN DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR SUBSEKTOR KOSMETIK DAN BARANG KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2023 - Desta Ariani; Lisa Hermawati; Andri Irawan (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2025)
The objective of this study is to determine the effect of Gross Profit Margin (GPM) and Return on Equity (ROE) on stock prices of cosmetics and household goods manufacturing subsector companies listed on the Indonesia Stock Exchange for the period 2018–2023. The analysis method employed is quantitative, using Panel Data Regression Analysis. The data for this research were sourced from the Indonesia Stock Exchange and the annual financial statements of cosmetics and household goods manufacturing subsector companies. The results show that simultaneously (F-test), Gross Profit Margin and Return on Equity have a significant effect on stock prices. Partially (t-test), Gross Profit Margin has a positive but insignificant effect on stock prices of cosmetics and household goods manufacturing subsector companies listed on the Indonesia Stock Exchange for the period 2018–2023. Meanwhile, Return on Equity has a positive and significant effect on stock prices. The regression coefficient for Gross Profit Margin is positive, indicating a direct relationship between Gross Profit Margin and stock prices. Similarly, the regression coefficient for Return on Equity is also positive, indicating a direct relationship between Return on Equity and stock prices. The coefficient of determination indicates that the contribution of Gross Profit Margin (GPM) and Return on Equity (ROE) in explaining variations in stock price changes is 24.88%, while the remaining 75.12% is explained by other variables not included in this study, such as Current Ratio, Debt to Equity Ratio, and others.